2006
DOI: 10.1515/jpm.2006.052
|View full text |Cite
|
Sign up to set email alerts
|

Altered protease expression by periarterial trophoblast cells in severe early-onset preeclampsia with IUGR

Abstract: Adaptation of uteroplacental arteries in patients with early-onset preeclampsia combined with IUGR is compromised due to insufficient invasion of extravillous trophoblast cells (EVT) into the spiral artery wall. The underlying molecular mechanisms are widely unknown. We investigated expression and possible mechanisms of regulation of different matrix-metalloproteases (MMPs) by EVT in placental bed biopsies from patients with early onset preeclampsia combined with IUGR and healthy pregnant women. Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 29 publications
1
38
0
2
Order By: Relevance
“…This is consistent with other studies which have examined MMP3 levels in the amniotic fluid and fetal membranes in women with preterm labor and PROM (Fortunato et al 1999b, Park et al 2003. Further, Reister et al (2006) have reported reduced expression of MMP3 in extravillous trophoblast cells obtained from placental bed biopsies from patients with early-onset preeclampsia combined with IUGR. However, to our knowledge our study for the first time examines the placental levels of these MMPs in preterm deliveries.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other studies which have examined MMP3 levels in the amniotic fluid and fetal membranes in women with preterm labor and PROM (Fortunato et al 1999b, Park et al 2003. Further, Reister et al (2006) have reported reduced expression of MMP3 in extravillous trophoblast cells obtained from placental bed biopsies from patients with early-onset preeclampsia combined with IUGR. However, to our knowledge our study for the first time examines the placental levels of these MMPs in preterm deliveries.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the influx of NK cells during decidualisation and their subsequent role in interacting with invasive EVTs and spiral artery cells could be impaired, supported by immunohistochemical studies showing reduced decidual leukocytes in pre-eclampsia (Williams et al 2009a). Other factors of importance in regulating trophoblast invasion such as EVT expression of a particular adhesion molecule repertoire (Zhou et al 1997a), levels of MHC class I molecules such as HLA-G (Le Bouteiller et al 2003), increased apoptosis (Genbacev et al 1999) or production of MMPs (Reister et al 2006) have also been suggested. The signalling events that occur firstly between leukocytes and vascular cells and then subsequently between trophoblasts and vascular cells may also be impaired; however, this remains to be comprehensively investigated.…”
Section: Pre-eclampsiamentioning
confidence: 98%
“…132 These findings might appear counterintuitive upon initial inspection, because low SOCS3 expression would in turn portend high STAT3 activation, and thus sufficient trophoblast invasion. However, the finding that the expression of the LIF-receptor is abnormally persistent on EVT cells from placental bed biopsies stemming from patients suffering from a combination of early onset pre-eclampsia and intrauterine growth retardation 133 only further denotes the importance of LIF and SOCS3 fine-tuning. In conclusion, it seems that the LIF-JAK-STAT-SOCS signalling pathway is involved in many functions of the trophoblast and their derivate cells as can be recognized in murine models, in vitro assays and descriptional studies.…”
Section: -105mentioning
confidence: 99%